Production and secretion of recombinant spider silk in Bacillus megaterium - Alexander Connor; R. Helen Zha; Mattheos Koffas (Microbial Cell Factories, 2024)
Abstract Background Silk proteins have emerged as versatile biomaterials with unique chemical and physical properties, making them appealing for various applications. Among them, spider silk, known for its exceptional mechanical strength, has attracted considerable attention. Recombinant production of spider silk represents the most promising route towards its scaled production; however, challenges persist within the upstream optimization of host organisms, including toxicity and low yields. The high cost of downstream cell lysis and protein purification is an additional barrier preventing the widespread production and use of spider silk proteins. Gram-positive bacteria represent an attractive, but underexplored, microbial chassis that may enable a reduction in the cost and difficulty of recombinant silk production through attributes that include, superior secretory capabilities, frequent GRAS status, and previously established use in industry. Results In this study, we explore the potential of gram-positive hosts by engineering the first production and secretion of recombinant spider silk in the Bacillus genus. Using an industrially relevant B. megaterium host, it was found that the Sec secretion pathway enables secretory production of silk, however, the choice of signal sequence plays a vital role in successful secretion. Attempts at increasing secreted titers revealed that multiple translation initiation sites in tandem do not significantly impact silk production levels, contrary to previous findings for other gram-positive hosts and recombinant proteins. Notwithstanding, targeted amino acid supplementation in minimal media was found to increase production by 135% relative to both rich media and unaltered minimal media, yielding secretory titers of approximately 100 mg/L in flask cultures. Conclusion It is hypothesized that the supplementation strategy addressed metabolic bottlenecks, specifically depletion of ATP and NADPH within the central metabolism, that were previously observed for an E. coli host producing the same recombinant silk construct. Furthermore, this study supports the hypothesis that secretion mitigates the toxicity of the produced silk protein on the host organism and enhances host performance in glucose-based minimal media. While promising, future research is warranted to understand metabolic changes more precisely in the Bacillus host system in response to silk production, optimize signal sequences and promoter strengths, investigate the mechanisms behind the effect of tandem translation initiation sites, and evaluate the performance of this system within a bioreactor.